Anaerobic co-digestion of municipal waste sludge with grease trap waste mixture: Point of process failure determination. (July 2020) - Shakourifar, Niloofar; Krisa, David; Eskicioglu, Cigdem
Abstract: Using high-strength wastes, such as grease trap waste mixture (GTWM) from multiple commercial facilities, as a co-substrate in anaerobic digestion can contribute to a significant increase in methane production. However, challenges such as long chain fatty acids (LCFAs) accumulation, sludge flotation, washout and scum formation can lead to digester failure. In this study, the optimal operating condition to achieve the highest methane production from an anaerobic, semi-continuous flow, mesophilic co-digester at a solids retention time of 20 days was determined. The ratio of GTWM/sludge was increased based on volatile solids (VS) concentration from 10% to 50% in 10% increments. A 40% GTWM/sludge ratio was determined to be optimum in which up to 22%, 200% and 68% improvements in VS removal, daily biogas production and specific methane production, respectively, were observed with respect to control utilizing sludge only. Beyond a 40% GTWM/sludge, the anaerobic co-digester experienced failure and addition of biochar to mitigate LCFA inhibition to failing co-digester could not recover the process. Digester LCFA concentrations were also measured during stable and unstable digester operations. Highlights: Grease trap waste (GTW) increased daily biogas yield from sludge digester by 200%. Beyond 40% GTW/sludge ratio (volatile solids basis), digester failure was observed. GTW had no impact on digestate fecal coliform, dewaterability and heavy metals. In batch assays, biochar removed inhibitory long chain fatty acids from digestate.